IMPLEMENTASI DAN ANALISIS ALGORITMA STEMMING NAZIEF & ADRIANI DAN PORTER PADA DOKUMEN BERBAHASA INDONESIA - Dwi Wahyudi; Teguh Susyanto; Didik Nugroho (STMIK Sinar Nusantara, 2017)
Stemming is a process to return a derivative word into its root word by eliminating the affixes. This is necessary to support a better information retrieval system. Some research on stemming algorithm, including algorithm Nazief & Adriani and Porter. Each stemmer has advantages and disadvantages of each. The purpose of this study is to compare the two stemmers, so it is known which algorithm is better to support information retrieval system. This research mostly applied literature study with reference to research conducted by Asian Jelita and Fadillah Z Tala. Test documents obtained from online news sites (detik.com). The process of analysis is done by calculating the number of correct results and experiencing stemming errors (over stemming, under stemming, unchanged, spelling exception), then comparing the result and time of the process, so it will be known which stemmer is better to support information retrieval system.